2019
DOI: 10.1039/c9sc04222a
|View full text |Cite
|
Sign up to set email alerts
|

HAMA: a multiplexed LC-MS/MS assay for specificity profiling of adenylate-forming enzymes

Abstract: Adenylation enzymes are engineering targets in ribosomal and nonribosomal peptide synthesis. Through multiplexed LC-MS/MS measurement of hydroxamates, the HAMA assay records specificity profiles of these enzymes in a snap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 42 publications
0
45
0
Order By: Relevance
“…We have shown that testing a small number of reversions to residue identities before swapping can generate significant improvements. 40 In this fashion, substrate specificity has been increased in the MS mutant and the temperature tolerance has been extended by 10 °C in the STAP mutant (Figure 3a). Since subdomain swapping only directly affects a limited number of interface residues, screening of reversion mutations comes at a low cost and may be more generally applicable to chimeric NRPS domains.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We have shown that testing a small number of reversions to residue identities before swapping can generate significant improvements. 40 In this fashion, substrate specificity has been increased in the MS mutant and the temperature tolerance has been extended by 10 °C in the STAP mutant (Figure 3a). Since subdomain swapping only directly affects a limited number of interface residues, screening of reversion mutations comes at a low cost and may be more generally applicable to chimeric NRPS domains.…”
Section: Discussionmentioning
confidence: 89%
“…In the DKP formation assay used for screening, the STAP mutant showed a 6-fold increase in activity with slightly lower Val-selectivity (37%) and the MS mutant showed 2-fold higher activity at increased Val-selectivity (91%) compared to sdV-GrsA (54%, Supplementary Figure 6). 40 Thermal stability. Since sdV-GrsA is an unstable, chimeric protein impaired by engineering, we suspected improved structural integrity as a driver of evolutionary improvements.…”
Section: Resultsmentioning
confidence: 99%
“…In M. alpina, malpibaldin A (L-Phe derivative) is the major compound (17). Such discrepancies between adenylation preference and relative product formation rate may be caused by side-chain specificity of downstream reaction steps or differences in intracellular amino acid availability (51). Promiscuous adenylation leading to the parallel production of multiple products from one NRPS assembly line has been well studied in cyanobacterial enzymes and may be an important springboard for evolutionary diversification (45,54).…”
Section: Adenylation Domains Of Mpca and Mpba Activate L-amino Acidsmentioning
confidence: 99%
“…The hydroxamate formation assay was conducted as previously described (51). In brief, the assay was carried out at room temperature in 100 µL volume containing 50 S13).…”
Section: Multiplexed Hydroxamate Based Adenylation Domain Assay (Hama)mentioning
confidence: 99%
“…6 As a consequence, several strategies have been tested to edit the specificity of the A-domain. [7][8][9][10][11] Alternatively, domains and modules have been substituted and reshuffled. [12][13][14][15] One key emerging issue is the substrate tolerance of follow-up domains after changing the peptide sequence.…”
Section: Introductionmentioning
confidence: 99%